Gastrocnemius Muscle Histopathology In Spastic Rats - Marina Indriasari, MD,Phd; Ferial Hadipoetro; Bambang Pontjosoeryanto (Indonesian Journal of Physical Medicine & Rehabilitation, 2022)
ABSTRACT Introduction: Spasticity caused by the injury of the central nervous system. Muscle with spasticity causes muscle fibers to change in size and distribution. Methods: To analyze the structure of the spasticity of the muscles, study use the excisional biopsy of the gastrocnemius muscle of spastic rats. Experimental study was conducted on 42 spastic rats in 6 groups with different doses of calcium. Staining of gastrocnemius muscle tissue fibers using hematoxylin-eosin.Calcium staining using alizerin red. Results: Hematoxylin-eosin staining shown the muscle cell nucleus, cytoplasm or endoplasm appears roseate. Analysis of the spastic condition found that the distance between the muscle fibers dilated and the diameter smaller. Calcium deposits appear in spastic muscle tissue, by purplish-blue. The pearson correlation test showed a significant correlation between muscle fiber distance and spasticity after intervention (p<0.05). The spearman correlation test showed a significant correlation between spasticity after intervention (p=0.008) and each changes in spasticity (p=0.015). Conclusions: HE staining used to determine the arrangement of muscle tissue in spastic gastrocnemius muscles and alizerin red determined calcium deposits in spasticity muscle tissue. There is a significant correlation between the distance between muscle fibers with spasticity and between changes in spasticity after the intervention.Keywords: alizerin red staining, gastrocnemius muscle, hematoxylin-eosin staining, histopathology, spastic rats